Detecting Gender Discrimination in the Layout of Residential Buildings: A Comparative Analysis - iftikhar, Sehar; Ullah, Ubaid; Ammar, Malik Fazal (Annals of Human and Social Sciences, 2024)
This paper explores the significance of considering the needs and preferences of female residents in house designs to address housing demands effectively and ensure user satisfaction. Drawing on research from various disciplines, it highlights the critical role of housing in individuals' lives, encompassing social interactions, employment, education, and family dynamics. The study emphasizes the importance of user-centric design and active participation of housewives in decision-making to create homes that accommodate diverse responsibilities and lifestyles. Utilizing space syntax analysis, the research investigates the spatial organization of homes in Abbottabad, comparing architect-designed layouts with those configured by female homeowners. Findings reveal disparities in spatial arrangements, emphasizing the need for flexible and well-connected spaces, particularly in key areas such as kitchens and lounges. Recommendations are provided for future housing designs, including seamless integration of outdoor spaces, consideration of cultural factors, and establishing feedback mechanisms with users to ensure designs evolve to meet changing needs. Overall, the paper advocates for collaborative efforts between designers and users to create sustainable and user-centric homes that reflect the unique behaviors and preferences of female residents.